Super-Wideband Monopole Printed Antenna with Half-Elliptical-Shaped Patch - Fitri Yuli Zulkifli; Aditya Inzani Wahdiyat; Abdurrahman Zufar; Nurhayati Nurhayati; Eko Setijadi (Telecom, 2024)
Super-wideband (SWB) antennas have emerged as a promising technology for next-generation wireless communication systems due to their ability to transmit and receive signals across a wide frequency spectrum. A half-elliptical-shaped patch antenna for a super-wideband antenna is proposed in this paper. The proposed antenna was composed of a half-elliptical-shaped patch with a microstrip feedline and a partial ground plane with a triangular inset and a bent edge ground plane. This proposed antenna was designed using Taconic TLY-5 with a dielectric permittivity of 2.2 and a total dimension of 200 × 220 × 1.57 mm3. The proposed antenna demonstrates a bandwidth of 23 GHz (from 0.5 GHz to 23.5 GHz) with a bandwidth ratio of 47:1.